Curriculum Tranformation of Islamic Religious Education - Tri Marfiyanto (EDUTEC : Journal of Education And Technology, 2018)
In the context of Indonesia, especially after the New Order government, many changes occurred in the structure of our constitutional system. The transition of forms of government from centralized to decentralized, changes in democratic climate, the strengthening of the issue of human rights, a firmer recognition of cultural, religious and racial pluralism, all of which have implications for Government policies in the field of education. The aim of this paper is to reveale the transformation of curriculum in islamic religion education. This study used literature review. The result of this paper that there has been a paradigm shift in the PAI curriculum in public universities after the New Order government, especially in the 2002 PAI curriculum. The paradigm developed sees Islam as a dynamic and responsive perspective towards the present.